If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2c + 5 = 3c + 7 Reorder the terms: 5 + 2c = 3c + 7 Reorder the terms: 5 + 2c = 7 + 3c Solving 5 + 2c = 7 + 3c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-3c' to each side of the equation. 5 + 2c + -3c = 7 + 3c + -3c Combine like terms: 2c + -3c = -1c 5 + -1c = 7 + 3c + -3c Combine like terms: 3c + -3c = 0 5 + -1c = 7 + 0 5 + -1c = 7 Add '-5' to each side of the equation. 5 + -5 + -1c = 7 + -5 Combine like terms: 5 + -5 = 0 0 + -1c = 7 + -5 -1c = 7 + -5 Combine like terms: 7 + -5 = 2 -1c = 2 Divide each side by '-1'. c = -2 Simplifying c = -2
| 67-5x=9x+7 | | 3a-11=4 | | 60-x=2(x-36) | | 2x+6=-3 | | 104-x=2(x-29) | | 20x-9x-20=0 | | 3x+139=12x-14 | | x-9x-20=0 | | 4x-2=11x-43 | | 49-6x=12x+15 | | 5m(2m-7)=-5 | | -8x-y=-8 | | x^3-8x^2+15x+12=0 | | 2x^2-11x-24=0 | | 2(x+3)-3=8-2x | | -21-9x=-32-9x | | 114-3x=24x+18 | | 8-7x=93-42x | | 7,000,000a=10 | | -8b-10=-7-6b | | -2(7w-5)+4w=2(w+2) | | 48x^2=0 | | -4-5x=8-4x | | 81+5y=-4y | | 2(6t+1)-4(t-1)= | | M^2-13m+26= | | 1/4-1/5= | | 10+9x=98-x | | 7+c=40 | | (c+4)(c-3)+6(1+c^2)=(c-2)(c+2) | | 213-4x=32x+21 | | 1/5(3x+12)=3(1-4x)+12 |